Histological and molecular characterization of Edwardsiella anguillarum infection in tilapia (Oreochromis niloticus) cultivated in the biofloc system in Lima, Peru - Sierralta, Veronica Anamaría (2020)
The aim of this study was to isolate and characterize phenotypically and molecularly the pathogen Edwardsiella anguillarum, as well as to determine the anatomo-histopathological lesions in tilapia (Oreochromis niloticus) cultivated with biofloc technology in the northern area of Lima, Peru. Five isolated bacterial strains were isolated and characterized by conventional biochemical techniques and by the API 20E system. E. anguillarum was identified from internal organs using biochemical and molecular techniques. The most frequent external clinical signs were bilateral exophthalmia, erythema in the pectoral fins and around the anus. Internally, whitish nodules in the heart and liver were observed. The histopathological study revealed necrosis in the branchial lamellae, spleen, intestine, posterior kidney and gonad, as well as the presence of an inflammatory reaction of granulomatous type in the heart, liver, spleen, kidney and gonads. The strains showed fermentative glucose metabolism and positivity to methyl red, production of hydrogen sulphide, indole and acid production from mannitol. The isolates were confirmed by the PCR technique and sequencing of the 16S rRNA gene. All the strains showed sensitivity to the antibiotics nalidixic acid, florfenicol, gentamicin, kanamycin, flumequine, oxytetracycline and trimethoprim sulfamethoxazole.